Cysteine‐rich secretory protein 3: inflammation role in adult varicocoele. (24th October 2018) - Belardin, L.; Camargo, M.; Intasqui, P.; Antoniassi, M.; Fraietta, R.; Bertolla, R.
Abstract: Background: Cysteine‐rich secretory protein (CRISP‐3), a protein involved in inflammatory response, is highly increased in seminal plasma of adolescents with varicocoele and altered semen analysis, but not in adolescents with varicocoele and normal semen. It is not known, however, whether this increased seminal concentration occurs as an acute marker during the initial stages of varicocoele or whether this persists as an altered protein pathway. Objective: The purpose of this study, thus, was to test the hypothesis that this inflammatory state persists through adulthood and the correction of varicocoele could correct this state, by identifying the levels of CRISP‐3 in seminal plasma. Materials and methods: This study was carried out in two substudies: (i) to verify the effect of varicocoele and (ii) to verify the effect of varicocelectomy on seminal plasma CRISP‐3 levels. Seminal plasma CRISP‐3 levels (29 and 31 kDa isoforms) were assessed for each provided sample using standard Western blotting. Results: The varicocoele group presented higher seminal levels of CRISP‐3 when compared to controls, with a 67.5‐fold increase in the unglycosylated isoform (29 kDa) and a 5.2‐fold increase in the glycosylated isoform (31 kDa). In contrast, CRISP‐3 levels decreased following varicocelectomy, both in the unglycosylated (5.6‐fold decrease) and in the glycosylated (4.3‐fold decrease) isoforms. Discussion: CRISP‐3, a protein involved in inflammation, is increased in seminal plasma of men with varicocoele and this is partially reversed by varicocelectomy. Monitoring its seminal levels may be useful for assessing inflammation‐related alterations to fertility in men with varicocoele. Conclusion: We conclude that, in the presence of varicocoele, there is a marked increase in seminal CRISP‐3 levels. Surgical intervention (varicocelectomy) decreases CRISP‐3 levels and improves semen quality.